2012
DOI: 10.1089/ind.2011.0012
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Induced Crystallization as a Sustainable Method for Product Recovery of Building Block Chemicals: Techno-Economic Evaluation of Fumaric Acid Separation

Abstract: Carboxylic acids are key platform chemicals for use as biobased alternatives for fossil-based applications. State-of-the-art fermentations of carboxylic acids at neutral pH with downstream product recovery by pH-shift crystallization are not sustainable due to the accompanied production of waste salts. To earn the label''sustainable,'' salts should be converted into the original base and acid required for fermentation and product recovery. This paper shows that electrochemically induced crystallization (EIC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Nasrollahnejad et al continued this work with at echnoeconomic evaluation of the proposed process for the production of fumaric acid. [58] They compared conventional fermentativep roduction, production and subsequent salt regeneration, and productiont hrough electrochemically induced crystallization. The conventional methodr equired af inal pH shift to induce the crystallization of fumarica cid in the bulk phase, whichp roduced about 1.3 tons of solid waste per ton of product.…”
Section: Crystallization Of Compound-forming Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasrollahnejad et al continued this work with at echnoeconomic evaluation of the proposed process for the production of fumaric acid. [58] They compared conventional fermentativep roduction, production and subsequent salt regeneration, and productiont hrough electrochemically induced crystallization. The conventional methodr equired af inal pH shift to induce the crystallization of fumarica cid in the bulk phase, whichp roduced about 1.3 tons of solid waste per ton of product.…”
Section: Crystallization Of Compound-forming Systemsmentioning
confidence: 99%
“…Nasrollahnejad et al. continued this work with a technoeconomic evaluation of the proposed process for the production of fumaric acid . They compared conventional fermentative production, production and subsequent salt regeneration, and production through electrochemically induced crystallization.…”
Section: External Crystallizationmentioning
confidence: 99%
“…Furthermore, several works illustrate the synergies between electrified downstream processes and pH-control of fermentation processes [ 8 , 9 , 10 , 11 ]. However, these processes usually can not compete with conventional processes due to high operation costs or low stability of the membranes due to scaling or fouling [ 5 , 18 ]. In previous work, we showed that crystallization on the membrane can be prevented and pure succinic acid can be produced via electrochemical pH-shift crystallization [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several works illustrate the synergies between different electrochemical membrane processes and fermentations by producing base for the pH control of the fermentation, while simultaneously removing the product from the broth [13][14][15][16]. Techno-economical evaluations illustrate ecological advantages, but also conclude that membrane fouling and operating costs limit the economic feasibility of these approaches [3,5,7,16,17].…”
Section: Introductionmentioning
confidence: 99%